2013
DOI: 10.1126/scisignal.2003252
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Regulates Mitochondrial Fatty Acid Metabolism Through Reversible Protein S -Nitrosylation

Abstract: Cysteine S-nitrosylation is a posttranslational modification by which nitric oxide regulates protein function and signaling. Studies of individual proteins have elucidated specific functional roles for S-nitrosylation, but knowledge of the extent of endogenous S-nitrosylation, the sites that are nitrosylated, and the regulatory consequences of S-nitrosylation remains limited. We used mass spectrometry-based methodologies to identify 1011 S-nitrosocysteine residues in 647 proteins in various mouse tissues. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
225
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(239 citation statements)
references
References 35 publications
13
225
0
1
Order By: Relevance
“…Interestingly, our data suggest that O-ASCs promoted glycolysis in cancer cells by elevating NO synthesis, which has been shown to have inhibitory effects on enzymes involved in mitochondrial respiration. Previous studies showed that NO affects glycolysis through s-nitrosylation of hexokinase (37). Hexokinase converts glucose to glucose-6-phosphate in the first step of glycolysis and is highly expressed in cancer cells (38).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our data suggest that O-ASCs promoted glycolysis in cancer cells by elevating NO synthesis, which has been shown to have inhibitory effects on enzymes involved in mitochondrial respiration. Previous studies showed that NO affects glycolysis through s-nitrosylation of hexokinase (37). Hexokinase converts glucose to glucose-6-phosphate in the first step of glycolysis and is highly expressed in cancer cells (38).…”
Section: Discussionmentioning
confidence: 99%
“…Ischiropoulos and colleagues further utilized this phenylmercury-based SNO-capture approach to identify up to 1,000 S-nitrosylation sites on hundreds of proteins in various mouse tissues (64,65). The number of S-nitrosylation sites in vivo to nitric oxide were found to be substantially dependent on endothelial nitric oxide synthase (eNOS) or neuronal nitric oxide synthase (nNOS) (64,65).…”
Section: The Expanding Landscape Of the Thiol Redox Proteomementioning
confidence: 99%
“…FAS became more active following S-nitrosylation, indicating that S-nitrosylation plays an important role in adipogenesis. It has been reported that NO regulates mitochondrial fatty acid metabolism through protein S-nitrosylation regulation ( 40 ). Following a MS-based proteomics study, very long chain acyl-CoA dehydrogenase was proposed as a candidate S-nitrosylated protein involved in fatty acid HEK293 cells were transfected with FLAG-tagged FAS-WT or its cysteine mutants (C161A, C1127A, C1471A, and C2091A) and exposed to SNOC or old SNOC.…”
Section: Discussionmentioning
confidence: 99%
“…3B ). , and Cys 2091 have been predicted as candidate sites for FAS S-nitrosylation by a MS-based proteomics study ( 40 ). Thus, we examined whether these three cysteines might be involved in FAS S-nitrosylation.…”
Section: Dimerization and Activation Of Fas Are Mediated By Nomentioning
confidence: 99%